To identify and characterize an opioids-related adverse drug event (ADE) using naloxone as a trigger tool and to determine the causes of preventable ADEs - Phithakham, Cheeratikarn; Kritsadathan, Thanisa; Tiyaprasertkul, Worakamol; Phothikun, Ratcharin (Biomedical Sciences and Clinical Medicine, 2018)
Objective To identify and characterize an opioids-related adverse drug event (ADE) using naloxone as a trigger tool and to determine the causes of preventable ADEs. Methods An observation retrospective study was conducted by reviewing medical records of hospitalized patients who received naloxone from January 2015 to December 2016 at the University hospital. The researchers systemically reviewed the medical records to identify ADE cases which were further reviewed to determine whether they were preventable, and their causes as well as a severity rating. Results Out of the one hundred and eighty seven-cases reviewed, 31 events were identifi ed as ADEs (16.58 %). The incidence of opioids-related ADEs was 0.19 events per 100 admissions and 0.16 events per 1,000 patient-days. Twenty (64.52%) out of 31 events were identi fi ed as preventable ADEs. The severity of 19 events were classi fi ed as E. Inappropriate opioid doses was the most causes of preventable ADEs, which occurred during the prescribing phase (11 events, 55%) The majority of ADEs cases were female (70.97%) and the median age was 65 years (55-74). Morphine was the most frequently taken drug that caused ADEs (48.39). Conclusions Using naloxone as a trigger tool helps to increase the total number of identifi ed opioids-related ADEs. Most of these ADEs were classi fi ed as preventable ADEs. Preventable ADEs most often occurred during the prescribing phase.